Agricultural Resilience through Climate Services (ARCS): A manual for Training of Trainers (ToTs) - Rettie, Fasil M; Ndour, Adama; Gebremedhin, Amdom (International Maize and Wheat Improvement Center, 2025)
This training manual focuses on Training of Trainers (ToTs) and aims to equip them with the basic knowledge, skills, and communication channels framework required to disseminate effective agro-climate advisory (AgCA) services to smallholder farmers. The manual begins with the definitions and descriptions of AgCA, followed by purpose, key objectives, and other essential components. It covers the basics climate, including weather, climate, climate variability, and climate change along with their impacts on agricultural productivity. Recognizing the importance of establishing the value chain of partners and farming communities, the manual highlights participatory approaches and integrating local knowledge into actionable AgCA services in a comprehensive end-to-end manner.